2020
DOI: 10.1021/acsmedchemlett.9b00550
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a New Sulfonamide Hepatitis B Capsid Assembly Modulator

Abstract: Hepatitis B virus (HBV) remains a major health concern with 260 million people having been infected globally, and approximately 680,000 deaths have occurred annually from cirrhosis and liver cancer. The modulation of HBV capsid assembly has emerged as a promising therapeutic approach for curing chronic HBV infection. Small-molecule capsid assembly modulators (CAMs) can broadly be classified as heteroaryldihydropyrimidines and sulfamoylbenzamides (SBAs). SBAs are capsid activators that inhibit viral replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Our prior efforts to improve anti-HBV activity starting from NVR 3-778 and HAP_R01 yielded a structurally related but more potent compound, KR-26556. 22 Despite its cellular potency evidenced by reduced HBV DNA levels in HepAD cells, the present findings in HepG2.2.15 cells (Table 1, entry 15, EC 50 = 0.27 μM and CC 50 = 19.7 μM) revealed the need to develop more HBV-specific antiviral candidates. We aimed to synthesize more KR-26556 derivatives and identify alternative CAMs by investigating structure−antiviral activity relationships (SARs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior efforts to improve anti-HBV activity starting from NVR 3-778 and HAP_R01 yielded a structurally related but more potent compound, KR-26556. 22 Despite its cellular potency evidenced by reduced HBV DNA levels in HepAD cells, the present findings in HepG2.2.15 cells (Table 1, entry 15, EC 50 = 0.27 μM and CC 50 = 19.7 μM) revealed the need to develop more HBV-specific antiviral candidates. We aimed to synthesize more KR-26556 derivatives and identify alternative CAMs by investigating structure−antiviral activity relationships (SARs).…”
mentioning
confidence: 99%
“…The molecular docking studies with the HBV core protein (PDB code: 5T2P) showed that the proposed binding mode of 3 was similar to those of the cocrystallized ligand and 15 in our previous study (Figure 3). 22 The oxygen of the benzamide in 3 forms a key hydrogen bond with Trp102 (B chain), whereas Thr128 (C chain) forms additional hydrogen bonds with the nitrogen of the benzamide group. In addition, the piperidyl group of 3 points toward the solvent-exposed area.…”
mentioning
confidence: 99%
“…This inhibitor, developed by Roche, showed favorable safety, tolerability, and pharmacokinetics profile and has been classified as suitable for further clinical development [120]. This compound was also further successfully modified by installing functional moieties to increase the inhibitory activity of SBA_R01 as proved for sulfamoylbenzamide-based compound KR-26556 [121] (Table 2). Especially modifications of positions 4 and 6 with fluorine and methoxy group, respectively, resulted in significant improvement of the inhibitor potency.…”
Section: Hepatitis B Virus Assembly Inhibitorsmentioning
confidence: 99%
“…Representative HAPs (Bay 41-4109 and GLS4) and a SBA ENAN-34017 [80] also inhibited de novo synthesis of cccDNA. In recent years, discovery of new CAMs has markedly accelerated [83,[92][93][94]. Indeed, CAMs have been shown to disrupt amplification and formation of cccDNA [95,96].…”
Section: Nucleocapsid Assembly Modulatorsmentioning
confidence: 99%